2021
DOI: 10.1016/j.jlr.2021.100110
|View full text |Cite
|
Sign up to set email alerts
|

A liquid chromatography-mass spectrometry workflow for in-depth quantitation of fatty acid double bond location isomers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Moreover, the average RSD of the data shown in Figure is only 3% from three biological replicates (Table S6, Supporting Information). The same characteristics have been reported for lipid CC location isomer analysis from tissue, plasma, and single cells . The data reveal structural diversity of lipid molecular species down to the CC location level and highlight that CC location isomers are distributed heterogeneously among lipid species.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, the average RSD of the data shown in Figure is only 3% from three biological replicates (Table S6, Supporting Information). The same characteristics have been reported for lipid CC location isomer analysis from tissue, plasma, and single cells . The data reveal structural diversity of lipid molecular species down to the CC location level and highlight that CC location isomers are distributed heterogeneously among lipid species.…”
Section: Resultssupporting
confidence: 76%
“…A series of aryl ketones and aldehydes have been developed besides acetone, rendering flexibility in choosing the most suitable PB reagents for a specific application in lipid analysis ( 63 ). For instance, acetyl pyridines (3- and 2-acpy) have been developed as the charge-tagging/charge-switching PB reagents, which improve the LOI for nonpolar lipids including FAs, cholesteryl esters (CEs), and GLs down to the C=C location level ( 64 , 65 ). By coupling 2-acpy PB reaction with MS 3 or MS 4 -CID, the locations of C=Cs can be confidently determined with sn -chain specificity for GPLs ( 66 ).…”
Section: C=c Specific Derivatization Coupled With Ms/msmentioning
confidence: 99%
“…When the total quantity of the isomer is known, the concentration information can be further obtained. Examples of isomer quantitation following this principle have been shown for both C=C location isomers and sn -isomers ( 58 , 65 ). When the standards are not available, only “relative fractional quantitation” can be obtained because how the structural differences of the isomers might affect ionization and fragmentation is unknown.…”
Section: C=c Specific Derivatization Coupled With Ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…2′,4′,6′-Trifluoroacetophenone (triFAP) ( Figure 9 ) stood out among the ketones studied, providing an increase in the P–B reaction yield for different types of C=C bonds and high sensitivity (subnanomolar range) for C=C bond identification [ 87 ]. More recently, Xia and co-workers investigated the use of various acetyl pyridines, as well as pyridine derivatives of benzophenone, as derivatization reagents enabling charge reversal, and concluded that 2-acetylpyridine (2-acpy) ( Figure 9 ) leads to LODs in the subnanomolar range for MUFAs, PUFAs, as well as conjugated FAs [ 88 ]. The same derivatization reagent was applied for the determination of position-specific quantitative deuterium abundancies in bis-allylic deuterated highly unsaturated fatty acids (D-HUFA) (a novel class of drugs stabilized against H abstraction-mediated oxidation) by a shotgun lipidomics analysis [ 89 ].…”
Section: Derivatization Of Unsaturated Fatty Acids (Ufas)mentioning
confidence: 99%